Reduced Graphene Oxide and Nanoparticles Incorporated Durable Electroconductive Silk Fabrics. Issue 20 (26th August 2020) - Bhattacharjee, Shovon; Macintyre, Chandini Raina; Bahl, Prateek; Kumar, Uttam; Wen, Xinyue; Aguey‐Zinsou, Kondo‐Francois; Chughtai, Abrar Ahmad; Joshi, Rakesh
Abstract: Graphene derivatives have the capability of forming chemical bonding with fabrics and show the potential to be used in smart textiles. However, the challenge is to fabricate highly conductive multifunctional fabric with good washing durability. Herein, reduced graphene oxide (RGO) and silver (Ag)/copper (Cu) nanoparticles (NPs)‐coated durable electroconductive silk fabric is fabricated by facile dip and dry method using 3‐glycidyloxypropyl trimethoxy silane as coupling agent (CA). Results show that RGO and NPs‐coated fabrics not only demonstrate low surface resistance but also excellent electrothermal property, UV shielding, enhanced thermal stability, and outstanding hydrophobicity consistently in the following order: pure silk < silk‐RGO < silk‐CA‐RGO < silk‐CA‐RGO‐Ag < silk‐CA‐RGO‐Cu. The addition of CA and NPs is found to have a significant impact on performance and washing durability. Cu incorporated samples (silk‐CA‐RGO‐Cu) show a very low value of surface resistance (3.15 kΩ sq −1 ) and even after washing 20 times, the resistance (6.76 kΩ sq −1 ) is observed to be lower than unwashed non‐Cu incorporated samples. Moreover, silk‐CA‐RGO‐Cu also has the highest UV resistance, Joule heating, hydrophobicity, and thermal stability among all samples, which makes it well suited for numerous potential applications including protective clothing, health monitoring, motion sensing, and sports clothing. Abstract : RGO and silver (Ag)/copper (Cu) nanoparticles‐coated durable silk fabric is fabricated by using 3‐glycidyloxypropyl trimethoxy silane as a crosslinking agent. Developed fabrics demonstrate excellent electrothermal, UV shielding, thermal stability, and hydrophobic property. Fabrics coated with RGO and Cu show the best performance and highest washing durability. Overall, the developed fabrics show huge potential to be used as a smart textile.